A mathematical model for the use of energy resources: a singular parabolic equation - Daniel López-García; Rosa Pardo (Mathematical Modelling and Analysis, 2020)
We consider a singular parabolic equation, for , arising in symmetric boundary layer flows. Here is a bounded domain with C2 boundary is bounded, and T > 0 is some fixed time. We establish sufficient conditions for the existence and uniqueness of a weak solution of this singular parabolic equation with Dirichlet boundary conditions, and we investigate its regularity.